POTENSI STARTUP DIGITAL UNTUK SUSTAIN PADA MASA PANDEMI CORONA DI INDONESIA - Djayaputra, Frelin Ivana; Juliet, Lisa; A.R, Farrah Jihan; Maharani, Satyaning; Lauwren, Nastasya; P. A, Zalshabila Audrea; W., Michelle Anastasia (Jurnal VICIDI, 2020)
In today's all-digital era, many digital startups are starting to emerge and develop in Indonesia, but there are still problems that surround the development of digital startups in Indonesia, such as lack of access to capital, human resources, and unfavorable conditions such as the corona pandemic that occurred when this. This corona pandemic has made many digital startups feel a fairly large impact, both positively and negatively, from many people who went bankrupt due to the impact of the COVID-19 pandemic to many digital startups who have benefited from Work From Home (WFH) activities. Based on market needs that are different from usual due to the impact of the corona, digital startups are starting to design strategies so that they do not lose too much due to the impact of the COVID-19 pandemic, by creating strategies it will be seen which digital startups have the most potential to sustain in the future. the corona pandemic in Indonesia, this research focuses on the potential of digital startups to sustain during the corona pandemic in Indonesia. The results of this study are expected to find out which digital startups have the most potential to remain sustainable during the corona pandemic in Indonesia. Keywords : Digital startup, survival, COVID-19, sustain